Privacy enhancing method for dummy-based privacy protection with continuous location-based service queries - Hai LIU; Xing-hua LI; Er-meng WANG; Jian-feng MA (Tongxin xuebao)
Without need for the third party and sharing key, the dummy-based privacy protection scheme enabled users to obtain the precise query result in location-based services. However, in continuous queries, since the existing dummy-based privacy protection schemes ignored the spatio-temporal relevance of the submitted neighbor location sets, the ad-versary could infer dummies, making that the protection degree of users' location privacy was reduced. To solve this problem, a dummy-based privacy protection enhancing method toward continuous queries was proposed. In the proposal, the candidate dummies were first generated by the existing dummy-based schemes, and could be filtered through the check of continuous reasonability and single privacy enhancement. Security analysis shows that, in the proposed method, the formed movement paths are indistinguishable in time and space, so that protecting the user's location privacy effectively in continuous queries. Moreover, extensive experiments indicate that its computation cost is limited, and compared with the scheme adopted to generate candidate dummies, the user's privacy protection is also enhanced in snapshot query.